A Review Simplicillium Lanosoniveum, Prospects as Biological Control Agents in Indonesia - ambar susanti; Anton Muhibuddin; Zulfikar Zulfikar; Hardian Susilo Addy (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
Simplicillium lanosoniveum is a species of Simplicillium, included in the Cordycipitaceae. This fungus is known to have a dual role as an entomopathogen against insect pests and antagonist against disease pathogens in plants. There are no reports on the negative impact of S. lanosoniveum as biological control. In Indonesia, the research on the two roles of S. lanosoniveum is still limited. Therefore, it is necessary to study the potential of these fungi to be worthy of analysis, based on the results of previous research. The purpose of this study is to provide information about the potential of Simplicillium lanosoniveum as an entomopathogenic fungus and antagonist against plant fungal pathogens, which has various characteristics of pests and diseases in tropical regions.It is hoped that it can increase the diversity of fungi that act as biological agents in Indonesia, in an effort to suppress the use of chemical pesticides.